Dinamika Interaksi Sosial di Lingkungan Madrasah Ibtidaiyah Nurul Yaqin Surabaya - Ixfina, Ficky Dewi (Prodi PGMI STAI At-Tahdzib Ngoro Jombang, 2024)
This research aims to explore the roles of teachers and school policies in shaping the dynamics of social interaction at MI Nurul Yaqin Surabaya. Through qualitative methods involving interview data collection, observation, and documentation, information was gathered to analyze the factors influencing student interaction within the madrasah environment. The findings indicate that the inclusive and responsive role of teachers to students' needs, along with a conducive classroom environment, significantly contribute to the dynamics of social interaction in the classroom. Additionally, the implementation of supportive school policies, such as extracurricular activities, plays a crucial role in fostering positive interactions among students. However, challenges exist in dealing with student diversity, differences in learning abilities, and communication barriers among students. Therefore, focused and integrated efforts among teachers, the classroom environment, and school policies are necessary to create an inclusive and dynamic learning environment that supports positive social interaction at MI Nurul Yaqin Surabaya.